The application of virtual reality training for anastomosis during robot-assisted radical prostatectomy - Fubo Wang; Chao Zhang; Fei Guo; Xia Sheng; Jin Ji; Yalong Xu; Zhi Cao; Ji Lyu; Xiaoying Lu; Bo Yang (Asian Journal of Urology)
Objective: To investigate the application of virtual reality training in vesicourethral anastomosis during robot-assisted radical prostatectomy (RARP). Methods: Three certified robotic urologists who underwent virtual reality training were enrolled in the study group. The other three without training were enrolled in the control group. Parameters were recorded before and after the training. Then a total of 18 patients undergoing RARP were enrolled and randomized assigned to receive anastomosis procedures with certified urologists who either obtained or did not obtain training. The quality of the anastomosis was evaluated. Results: For the virtual training evaluation, the overall score was significantly improved from 65.0±10.8 to 92.7±3.5 (p=0.014); the time of anastomosis was shortened; the economy of motion improved; instrument collisions decreased after training (p<0.05). Besides, the effectiveness of the virtual training was evaluated in the 18 real anastomosis procedures which were completed either by three urologists with training or three urologists without training. Most intriguingly, the average time of anastomosis was shortened from 40.0±12.4 min to 25.1±7.1 min (p=0.015). The parameters including time of operation, creatinine level of drainage, postoperative hospital stay and duration of catheter drainage were comparable before and after training. Two leakages, which were observed in procedures by doctors without training, needed salvage sutures by a senior doctor. Conclusions: Virtual reality training enabled surgeons to become quickly familiar with robotic system manipulation, improved their skills for vesicourethral anastomosis and shortened the learning curve, thus helping them operate with high efficacy and quality.